An Original Approach for Translating Grafcet into C/Unix Code for Validation Purposes - Benaouda, N.; Benaouda, A. (Engineering, Technology & Applied Science Research, 2022)
This paper proposes an approach to simulate the function of the control part of a Grafcet model, translating it into C code in a Unix environment. First, the Grafcet/C generation schemes are established. The Grafcet model, described in graphic or text form, is transformed in an internal form and then to C code by a generation algorithm based on the previously found diagrams. The result is a program that simulates the operation of the automation in question and makes it possible to validate the functional specifications of sequential automation. This validation can be used for educational purposes, such as the learning of the Grafcet formalism, or corrective or evolutionary maintenance. Once the configuration, testing, and validation of the program are complete, it is possible to implement the object code on the microcontroller of the control system.